Analisa dan Perancangan Sistem Informasi Elearning Berbasis Web untuk Memantau Aktivitas Belajar Peserta Didik di SMP Fioretti Tigaraksa - Takyudin, Ahmad; Faturrahman, Husain; Juwono, Juwono; Julianto, Muhammad Rizky; Yulianti, Yulianti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2021)
An effective learning system is a learning system that combines collaboration between teachers, students and parents. Many schools are still using traditional methods to manage data and school management, especially in terms of learning materials and managing student grades, so that schools and parents find it difficult to monitor the learning activities of students. For example at SMP Fioretti Tigaraksa, value management and curriculum management are still manual in inputting, the data managed by the school is input in stages without an application or system that regulates and stores it, so that parents, students or teachers find it difficult to monitor the learning activities of participants. such as grades data, curriculum data, learning materials and student attendance, all of these things are still done manually causing the risk of losing data is quite large in each school year. Web-based E-learning Information System can be used as a solution to problems in the field of education, especially to provide materials, student attendance and manage student grades. In this system a prototype is made that will be built in the future, this e-learning system is made to manage value management, attendance and curriculum so that teachers, students and parents of students can access and work together in monitoring student learning activities quickly and easily. efficient. This study provides results to improve student learning activities that can be done wherever they are or do not have to be at school and to connect and establish cooperation between schools, teachers, and parents of students as an important component of education to the student learning process at school.